Mapping is a prerequisite for elimination of filariasis and effective targeting of filarial ‘hot spots’ - Chand, Gyan (Pathog Glob Health, 2016)
OBJECTIVE: This study was undertaken to determine the prevalence of filarial infection in the districts of Madhya Pradesh, which were classified as non-endemic by the national program for control of filariasis. These districts showed evidence of clinical symptoms related to filariasis. To confirm the presence of filariasis, night blood surveys and entomological surveys were carried out to detect microfilaria in humans and filarial infection in vectors. MATERIALS AND METHODS: For microfilaria surveys, thick blood smears were prepared by taking 60 μL of blood between 8.00 and 11.00 pm and examined under a microscope. Vectors Culex quinquefasciatus were dissected for the filarial infection from the affected villages of four non-endemic districts. RESULTS: Prevalence of microfilaria in the four districts ranged from 3.8% in district Shivpuri to 11.2% in district Bhind (overall mf rate 6.9%, 95% CI = 6.2–7.7). Infection and infectivity rates among vectors were recorded from three districts which varied from 2 to 13% and from 1.3 to 3.6%. CONCLUSION: The study confirmed the presence of circulating microfilaria in non-endemic population of four districts, which has significant public health implications. To assess filarial endemicity and hot spots, precise filarial risk mapping using new efficient diagnostic tools is needed to reinforce and extend the strategy in other areas to achieve elimination of lymphatic filariasis.